1998
DOI: 10.1172/jci1504
|View full text |Cite
|
Sign up to set email alerts
|

Congenital hypothyroidism due to mutations in the sodium/iodide symporter. Identification of a nonsense mutation producing a downstream cryptic 3' splice site.

Abstract: A 12-yr-old hypothyroid girl was diagnosed at birth as athyreotic because her thyroid gland could not be visualized by isotope scanning. Goiter development due to incomplete thyrotropin suppression, a thyroidal radioiodide uptake of < 1%, and a low saliva to plasma ratio of 2.5 suggested iodide (I-) transport defect. mRNA isolated from her thyroid gland and injected into Xenopus oocytes failed to increase I- transport. Sequencing of the entire Na+/I- symporter (NIS) cDNA revealed a C to G transversion of nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
2
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 29 publications
2
58
2
3
Order By: Relevance
“…The resulting impairment in I − uptake in the thyroid leads to congenital hypothyroidism, which, unless treated early in life by TH administration, causes goiter and even mental retardation. Study of the 14 ITD-causing NIS mutations identified to date (27)(28)(29)(30)(31)(32)(33)(34)(35)(36) has been instrumental in the identification of residues key for NIS transport activity (5, 16, 17, 22-25, 37, 38). For example, the analysis of T354P revealed the role in NIS function of TMS9, where this mutation is located (23).…”
Section: Significancementioning
confidence: 99%
“…The resulting impairment in I − uptake in the thyroid leads to congenital hypothyroidism, which, unless treated early in life by TH administration, causes goiter and even mental retardation. Study of the 14 ITD-causing NIS mutations identified to date (27)(28)(29)(30)(31)(32)(33)(34)(35)(36) has been instrumental in the identification of residues key for NIS transport activity (5, 16, 17, 22-25, 37, 38). For example, the analysis of T354P revealed the role in NIS function of TMS9, where this mutation is located (23).…”
Section: Significancementioning
confidence: 99%
“…O alelo aberrante, derivado do pai, apresentava comprometimento codificando proteína inativa, enquanto o alelo materno exibia mutação que originava o NIS incompleto (31). No Japão, foram descritas várias outras famílias (figura 1) e duas novas mutações, que alteravam aminoácidos na proteína comprometendo sua habilidade em transportar iodeto (32,33).…”
Section: Diagnóstico Molecular Apresentação Clínicaunclassified
“…About half of these inherited thyroid diseases are caused by an iodide organification defect, characterized by the reduced ability to retain iodide in the thyroid gland. In thyroid follicular cells, iodide is actively transported inside through the sodium iodide symporter (Dai et al 1996, Pohlenz et al 1998. Covalent binding of the iodide to the tyrosine residues (iodide organification) within the thyroglobulin (Tg) molecule and its subsequent coupling yields the thyroid hormones thyroxine (T 4 ) and triiodothyronine (T 3 ).…”
Section: Introductionmentioning
confidence: 99%